Chopinowski impuls. Dzienniki Stefana Żeromskiego wobec twórczości Fryderyka Chopina - Karpińska, Karolina (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
The article Chopin’s impulse. Stefan Żeromski’s „Diaries” versus Fryderyk Chopin’s output shows writer’s fascination for Fryderyk Chopin and his work. The main emphasis is put on the strength of influence of particular elements of composition on the neurotic system of Stefan Żeromski. Besides, it touches upon the synthesis of arts which the artist often referred to in his Diaries.